Neurodiversity and education - Ellis, Paul (Head of teaching and learning); Kirby, Amanda; Osborne, Abby (Corwin, 2023)
Human brains are diverse - each one of us has a unique set of connections between billions of nerve cells. Neurodiversity is about us all. It is not an exclusive club or one condition, difficulty, difference, or disorder. Understanding more about the concept of neurodiversity helps us consider, respect and appreciate these differences. It helps us see potential rather than deficit. This clear and practical book, which is useful for all aspects of learning and education discusses how an emphasis on neurodiverse 'ability' can cultivate a better world"--